Rwanda Sweetpotato Super Foods Market Chains that work for women and for the poor. - Low, Jan W.; Bocher, T.; Sindi, K. (International Potato Center, 2015)
This flyer outlines the findings of the Rwanda Sweetpotato Super Foods Project, which sought to build an effective public-private sector partnership, and to investigate whether sweetpotato processed products are profitable and acceptable to urban consumers. The project was implemented in four districts in Rwanda (Rulindo, Gakenke, Muhanga and Kamonyi).